The Effect Of Waist Flexibility Training On Smashing Ability In Extracurricular Volleyball At State High School 10 In Bengkulu City - Marendra, M. Redho; Personi, Megi; Sumantri, Ajis (Journal of Physical Education and Sports, 2026)
This study aims to determine the relationship between waist flexibility and smash skills of volleyball players at State Senior High School 4 Bengkulu Selatan. Correlation research is a study that attempts to determine whether there is a relationship between two or more variables. The independent variable is waist flexibility with the dependent variable being smash skills. The type of sample in this study uses a total sampling technique. The sample is all 15 volleyball players at State Senior High School 4 Bengkulu Selatan. The instrument used in this study is a waist flexibility and smash skills test. The waist flexibility and smash skills test obtained rtable of 0.51 because the correlation coefficient between rxy = 0.79 > 0.51 and a contribution of 62.41%, which means the relationship between waist flexibility and smash skills of volleyball players at State Senior High School 4 Bengkulu Selatan is significant and large. Thus, the hypothesis that reads "there is a relationship between waist flexibility and smash skills of volleyball players at State Senior High School 4 Bengkulu Selatan" is accepted. This means that there is a relationship between waist flexibility and smash skills of volleyball players at State Senior High School 4 Bengkulu Selatan.